Japanese Pan-Asianism and the Philippines from the late 19th century to the end of World War II going to the Philippines is like coming home? - Matthiessen, Sven (Leiden Boston Brill, 2016)
"Examines the development of Japanese Pan-Asianism and the perception of the Philippines within this ideology. Due to the archipelago's previous colonization by Spain and the US, the Philippines was a special case among the Japanese occupied territories during the war. Matthiessen convincingly proves that the widespread pro-Americanism among the Philippine population made it impossible for Japanese administrators to implement a pan-Asianist ideology that centred on a return to Asian values"--
Includes bibliographical references (pages 229-241)and index.
Keywords: Regionalism -- Asia -- History; Japan -- Foreign relations -- 1868-1912.; Japan -- Foreign relations -- 1912-1945.; Japan -- Relations -- Philippines; Philippines -- Civilization -- American influences; Philippines -- Relations -- Japan